2019
DOI: 10.1093/gastro/goz004
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in the age of biologics

Abstract: Since the introduction of the first anti-tumor necrosis factor antibodies in the late 1990s, biologic therapy has revolutionized the medical treatment of patients with inflammatory bowel disease (IBD). Nevertheless, surgery continues to play a significant role in treating IBD patients. Rates of intestinal resection in patients with Crohn’s disease or colectomy in ulcerative colitis are reducing but not substantially over the long term. An increasing variety of biologic medications are now available to treat IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 155 publications
2
54
0
2
Order By: Relevance
“…[7][8][9] Despite these options, some patients with UC require a colectomy. 10 The highest colectomy rates are seen during the first few years after diagnosis. 11 Patients usually undergo colectomy due to acute severe UC (10%-60% of patients).…”
Section: Key Messagesmentioning
confidence: 99%
“…[7][8][9] Despite these options, some patients with UC require a colectomy. 10 The highest colectomy rates are seen during the first few years after diagnosis. 11 Patients usually undergo colectomy due to acute severe UC (10%-60% of patients).…”
Section: Key Messagesmentioning
confidence: 99%
“…The literature from a recent review of surgery in patients with IBD reported that, although biologics may delay the need for colectomy, 10.0%-30.0% of patients with UC will ultimately require surgery. 28 Our analysis of patient records showed that about 8.0% of patients requiring colectomy in the 12 months following the initiation of golimumab and adalimumab. Other studies reported in the literature support high rates of colectomy-free survival in patients receiving these biologics.…”
Section: Open Accessmentioning
confidence: 88%
“…It should be noted that while biologics tend to yield better outcomes than non-biologics, they overall carry a higher utilization cost and may not be considered cost-effective, particularly when used as a maintenance therapy [43]. In addition, the use of biologics instead of non-biologics may delay the need to perform surgical interventions, particularly in patients suffering from UC [44]. Furthermore, combination therapies using biologics antagonizing TNF-α and corticosteroids are associated with higher risk of serious infections [45].…”
Section: Discussionmentioning
confidence: 99%